OVERVIEW OF FREQUENCY OF ONLINE GAME USE ON ELEMENTARY SCHOOL STUDENTS' ACHIEVEMENT MOTIVATION - Anjani, Selly Retna; Mariyati, Lely Ika (International Journal Multidisciplinary (IJMI), 2025)
Objective: The purpose of this study was to determine the effect of the frequency of online game use on the achievement motivation of elementary school students. Method: 140 fourth and fifth grade students from SDN X in Sukodono District, Sidoarjo Regency were sampled using a purposive sampling strategy. The results showed a negative relationship (r = -0.379; p <.001) between the frequency of online game use and achievement motivation, according to the Pearson product-moment correlation analysis method. Results: The results showed a negative relationship (r = -0.379; p <.001) between the frequency of online game use and achievement motivation, according to the Pearson product-moment correlation analysis method. This means that students' achievement motivation decreases when the frequency of online game use increases, and vice versa. Novelty: One of the interesting and relevant internal factors among students today is the use of online games. Additional Background (not explicitly labeled in original): The current phenomenon shows that there is a lot of decline and low achievement motivation from elementary school level to the next level of education.